Analisis Finansial Usaha Perikanan Tangkap Bagan Apung: Studi Kasus Di Kelurahan Batu Putih Atas, Kota Bitung - Putri, Elsari Tanjung; Hamel, Samuel (Proceedings of The Vocational Seminar on Marine & Inland Fisheries, 2025)
The majority of fishermen in Batu Putih Atas Subdistrict, Bitung City, use lift nets (bagan apung) as their primary fishing gear. The uncertainty of fishing operations due to seasonal changes highlights the need for a thorough economic feasibility analysis. This study aims to evaluate the economic viability of lift net fishing activities. Data were collected through surveys and interviews, and analysed using a descriptive quantitative approach based on financial data. The results show that lift net fishing in Batu Putih Atas is financially profitable. The annual total revenue reached IDR 432,000,000, with a net profit of IDR 334,550,000. The total annual catch amounted to 1,440 buckets (equivalent to 72 metric tons), with anchovies comprising 65% of the catch. Based on the analysis of the Revenue-Cost Ratio (R/C ratio), Break-Even Price, Break-Even Production, and Payback Period, lift net fishing is considered economically feasible and viable for continued operation..